Recovery procedure for linear stapler mis‐insertion in the esophageal submucosal layer during intracorporeal esophagojejunostomy. Issue 2 (3rd January 2022) - Nakamura, Kenichi; Shibasaki, Susumu; Nakauchi, Masaya; Tanaka, Tsuyoshi; Inaba, Kazuki; Uyama, Ichiro; Suda, Koichi
Abstract: Introduction: Intracorporeal esophagojejunostomy is a technically demanding procedure, with many challenges. This study presents the anastomotic and technical complications associated with the mis‐insertion of a linear stapler into the esophageal submucosal layer and the recovery procedure for this complication. Materials and Surgical techniques: Of 100 intracorporeal esophagojejunostomy cases from 2017 to 2020, this complication occurred in three cases—one during functional end‐to‐end anastomosis and two during the overlap method. To recover, the residual esophageal mucosa was incised from the entry point to the top of the incomplete staple line, which was then reinforced by suturing in full thickness, including the incised mucosa. After reinforcement, the common stab incision was closed by the linear stapler or handsewn. As a result, none of the patients developed anastomotic leakage or stenosis. Discussion: Mucosal dissection and suturing for recovery for the anastomotic site may be an option to address cases of mis‐insertion of a linear stapler into the submucosal layer.